Empowering Women Through The Application of Prenatal Yoga in Overcoming The Disconveniences of Pregnancy in Teluk Kenidai Village - Isye Fadmiyanor; Ari Susanti; Rahimatul Uthia (Universitas Lancang Kuning, 2023)
Changes that occur during pregnancy are normal events or processes. Not infrequently the mother has not been able to adapt to these changes so that the mother feels uncomfortable, if not addressed wisely it will have an impact on worry and anxiety that can interfere with the mother's daily activities. Prenatal yoga is one way to overcome or reduce these complaints, preparing pregnant women physically, mentally and spiritually to face the birth process. Teluk Kenidai Village is located in Kampar district where the people there are not familiar with prenatal yoga. After doing prenatal yoga, the majority of pregnant women feel that there has been a change in their complaints, such as reduced back/waist pain, cramps and reduced nausea, headaches and other complaints. Prenatal yoga can also be done by pregnant women while at home, even though not all yoga movements can be memorized, but by still doing some easy yoga movements to help pregnant women to overcome complaints during pregnancy.